NUMERICAL SIMULATION ANALYSIS AND THE DRAG REDUCTION PERFORMANCE INVESTIGATION ON CIRCULAR CYLINDER WITH DIMPLES AT SUBCRITICAL REYNOLDS NUMBER - WANG GuoRong; LIAO ChongJi; HU Gang; ZHONG Lin; ZHANG Min (Jixie qiangdu)
In order to study the drag reduction performance of non-smooth circular cylinder,the SST k-ω turbulence model was been used to simulate the flow around a circular cylinder and studied the drag reduction performance of a circular cylinder at the subcritical Reynolds number Re= 40 000. The sensitivity analysis of dimples ’ structure parameters,which include the depth,the inner shape and the distribution of dimples is carried out to study the influence of various parameters on the drag reduction of the flow around a circular cylinder. The results show that the circular cylinder with dimples has a good effect on drag reduction. Drag coefficient and lift coefficient decrease with the increasement of dimple depth first and then decrease increase.Moreover,the circular cylinder with dimples has the best drag reduction effect when h = 0. 015 D. The average drag coefficient of the circular cylinder with cylindrical dimples is 0. 923 while the average drag coefficient of the circular cylinder with spherical dimples is 0. 94. The average drag coefficient of the circular cylinder with dimples by diamond distribution is 0. 923 while the average drag coefficient of the circular cylinder with dimples by rectangle is 0. 973.